(untitled) (Economic studies journal, 2023)
The aim of this study was to investigate the nature of relationship between trade openness, financial development and economic growth in Maghreb countries. In addition, it aimed to explore whether or not, interaction between trade openness and financial development effects economic growth in these countries. In order to achieve its objectives, the study used annual data for 4 Maghreb countries which are: Libya, Algeria, Tunisia and Morocco, covering the period 1990-2020. Moreover, it adopted panel FGLS method. The main findings of the study indicated a negative relationship between trade openness and economic growth. However, it showed a positive relationship between financial development and economic growth in these countries. Furthermore, the interaction between financial development and trade openness was found positively related to economic growth.